THE MACROECONOMIC RELATIONS OF ADVERTISING EXPENDITURE: AN ANALYSIS OF CENTRAL AND EASTERN EUROPEAN COUNTRIES - KOVÁCS, Kármen (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
This paper gives an overview of the macroeconomic relations of advertising expenditure. The paper critically reviews studies about how aggregate advertising expenditure is related to aggregate consumption, economic growth and economic cycles. The cause-and-effect relation between aggregate advertising expenditure and aggregate consumption is not clear. However, a change in advertising expenditure can serve as an indicator at the macro level. Further, the aggregate advertising expenditure of thirteen Central and Eastern European countries (CEECs) is analysed between 2006 and 2011, emphasizing the effect of the economic crisis that started in 2008. According to the findings, an unambiguous relationship between aggregate advertising expenditure and macroeconomic factors cannot be confirmed. However, investigating four CEECs in the longer term, almost all relations are significant. JEL Classification: E21, E32, M37